Mitral valve prolapsus as a rare cause of sudden cardiac death case presentation and review of literature: Ani kardiyak ölümün nadir nedeni olarak mitral kapak prolapsusu vaka sunumu ve literatür derlemesi - Alıcı, Mehmet Hayri; Ercan, Süleyman; Sarı, İbrahim and Oylumlu, Muhammed and Davutoğlu, Vedat (European Journal of Therapeutics, 2012)
Mitral valve prolapsus (MVP) is common heart valve disease which is often accepted as benign. Rarely arrhythmias, mitral insufficiency and infective endocarditis can be seen in this disease. Much more rarely, MVP can lead to sudden cardiac death. We want to report and discuss that successful resuscitation of sudden cardiac death of a young male patient who had MVP. After then implantable cardiac defibrillator (ICD) was implanted to him with documented ICD defibrillation of 17 times for ventricular tachycardia/fibrillation. There was no reason for malignant arrhythmia as the cause of ICD discharge other then MVP. As a rare cause of sudden cardiac death, we aimed to discuss MVP and review sudden death risk factors in this entity.